Topological triplon modes and bound states in a Shastry–Sutherland magnet - McClarty, P; Krüger, F; Guidi, T; Parker, S; Refson, K; Parker, A; Prabhakaran, D; Coldea, R (Springer Nature, 2017)
The twin discoveries of the quantum Hall effect1, in the 1980s, and of topological band insulators2, in the 2000s, were landmarks in physics that enriched our view of the electronic properties of solids. In a nutshell, these discoveries have tau ght us that quantum mechanical wavefunctions in crystalline solids may carry nontrivial topological invariants which have ramifications for the observable physics. One of the side effects of the recent topological insulator revolution has been that such physics is much more widespread than was appreciated ten years ago. For example, while topological insulators were originally studied in the context of electron wavefunctions, recent work has initiated a hunt for topological insulators in bosonic systems: in photonic crystals3-6, in the vibrational modes of crystals7, and in the excitations of ordered magnets8. Using inelastic neutron scattering along with theoretical calculations, we demonstrate that, in a weak magnetic field, the dimerized quantum magnet SrCu 2 (BO 3 ) 2 is a bosonic topological insulator with topologically protected chiral edge modes of triplon excitations.